Dining House Information System (Case Study: Tengku Di Ujung, Simeulue District) - Ayat Hasanul Alfarisi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2021)
The Tengku Diujung restaurant is one of the tourist destinations that is frequently visited by tourists because the restaurant has a mainstay menu that is in demand by many visitors, one of which is lobster noodles. However, each sales report still records data manually, sometimes experiencing errors due to inaccuracies in recording data. The formulations in this study are; how to manage all data on reports of receipts, orders, and sales or expenditures of goods, and whether employees are easy to find data, and how to manage data on receipts, orders, and sales or expenditures of goods. To complete the data needed in the preparation of this study, the authors use writing sources, namely; Library Research, Field Research, and Interviews and Observatories. From the results of the discussion on